Comparison of RNA-Seq analysis data between tracheal mite-infested and uninfested Japanese honey bees (Apis cerana japonica) - Suzuki, Akihiko; Kamakura, Masaki; Shiramata, Takuya; Nakaoka, Shinji; Sakamoto, Yoshiko (BMC research notes, 2023)
The purpose of this data set is to investigate differences in RNA-Seq transcriptome profiles between Acarapis woodi-infested and uninfested Japanese honey bees (Apis cerana japonica). The data set is strengthened by data collected from different body parts (head, thorax, and abdomen). The data set will support future studies of molecular biological changes in mite-infested honey bees. We collected 5 mite-infested and 5 uninfested A. cerana japonica workers from each of 3 different colonies (designated as A, B, and C). Workers were dissected into 3 body sites (i.e., heads, thoraces, and abdomen), and 5 of each body site were pooled together for RNA extraction, generating a total of 18 RNA-Seq samples (2 infection status × 3 colonies × 3 body sites). FASTQ data files of each sample that were generated by a DNBSEQ-G400 sequencer with the 2 × 100 bp paired-end sequencing protocol are available in the DDBJ Sequence Read Archive under accession number DRA015087 (RUN: DRR415616-DRR415633, BioProject: PRJDB14726, BioSample: SAMD00554139-SAMD00554156, Experiment: DRX401183-DRX401200). The data set is a fine-scale analysis of gene expression in the mite-infested A. cerana japonica workers because 18 RNA-Seq samples are separated by 3 body sites.